567 BEYOND THE INTIMA MEDIA THICKNESS ASSESSMENT: THE MEASUREMENT OF OVERALL ECHOGENICITY (GSM) OF CAROTID INTIMA MEDIA COMPLEX SHOWS A POSITIVE CORRELATION WITH ARTERIAL STIFFNESS OF HYPERTENSIVE PATIENTS. (15th December 2022) - Natale, Francesco; Loffredo, Francesco; Molinari, Riccardo; Covino, Simona; Alfieri, Roberta; Altobelli, Ippolita; Cimmino, Giovanni
Abstract: Beyond the Intima Media Thickness assessment: the measurement of overall echogenicity (GSM) of Carotid Intima Media Complex shows a positive correlation with Arterial Stiffness of hypertensive patients. According to the latest ESC guidelines on CVD prevention (2021) arterial stiffness still has a role in predicting future CVD risk and defining patients' CVD risk level. However, significative measurement difficulties make a widespread evaluation of the AS problematic, especially in the ambulatorial outpatient setting. The IMT measurement is no longer recommended in the CVD risk assessment due to lack of standardization in measurement protocol and low power to reclassify patients toward higher CV risk. Understanding the correlation between the structure and function of the large arteries can lead to an optimization of cardiovascular disease prevention strategies. At present, indices of arterial stiffness have not been associated with qualitative morphological characteristics of intima-media complex. The IM GSM is a relatively simple measurement that can be acquired during a carotid color-Doppler ultrasound exam. The aim of this study was to investigate the relationship between indices of arterial stiffness and echogenicity of intima media complex (IM GSM) of the common carotid arteries in subjects with arterial hypertension. In our study population of 421 hypertensive patients, subjects with IM GSM > 30 showed a significantly increased arterial stiffness and LVMI (P < 0.001). A weak positive correlation was found between IM GSM and SBP (r =0.35, < 0.001), and duration of hypertension (r = 0.31, < 0.01). Our study suggests that increased stiffness observed in hypertensives is associated with qualitative changes in carotid arterial wall.